EFEKTIVITAS PENGGUNAAN APLIKASI E-SURVEY TERHADAP PELAYANAN KEIMIGRASIAN BAGI WARGA NEGARA INDONESIA DI KANTOR IMIGRASI KELAS I TPI KUPANG - Isidorus Anung Prabadhi; Rasona Sunara Akbar; Justine Mariana Filitzia Waso (Polteknik Imigrasi, 2021)
Based on Law of Republik of Indonesia Number 25 of 2009 concerning public services, a public service provider must involve the community as a way or effort to build a fair, transparent and accountable system. The e-survey application provides convenience for users of immigration services in terms of accessing and providing an assessment of immigration services. Through this e-survey application, it is expected to improve the quality of immigration service performance to be better than before. This study aims to determine the effectiveness of the e-survey application on immigration services for Indonesian citizens at the Class I Checkpoint Immigration Office of Kupang, and what factors are supporting and inhibiting the effectiveness of using the e-survey application. The type of method used is descriptive qualitative - descriptive, with data collection carried out through interviews, observations, and documentation. Data analysis techniques are carried out by data reduction, data presentation, as well as drawing conclusions and verification. The results of this study indicate that the use of the e-survey application is running effectively, this is measured by using the four effectiveness indicators. The use of the e-survey application is supported by a QR-Code provided in banners and small boards. As well as to facilitate access for the public, free wifi is provided. While the inhibiting factor is unstable network conditions, not all applicants have smartphones and smartphones that don’t support QR-Code reading.